Pulmonary Iron Homeostasis in Hepcidin Knockout Mice - Deschemin, Jean-Christophe; Mathieu, Jacques R. R.; Zumerle, Sara; Peyssonnaux, Carole; Vaulont, Sophie (Frontiers in Physiology, 2017)
Pulmonary iron excess is deleterious and contributes to a range of chronic and acute inflammatory diseases. Optimal lung iron concentration is maintained through dynamic regulation of iron transport and storage proteins. The iron-regulatory hormone hepcidin is also expressed in the lung. In order to better understand the interactions between iron-associated molecules and the hepcidin-ferroportin axis in lung iron balance, we examined lung physiology and inflammatory responses in two murine models of systemic iron-loading, either hepcidin knock-out (Hepc KO) or liver-specific hepcidin KO mice (Hepc KOliv), which do (Hepc KOliv) or do not (Hepc KO) express lung hepcidin. We have found that increased plasma iron in Hepc KO mice is associated with increased pulmonary iron levels, consistent with increased cellular iron uptake by pulmonary epithelial cells, together with an increase at the apical membrane of the cells of the iron exporter ferroportin, consistent with increased iron export in the alveoli. Subsequently, alveolar macrophages accumulate iron in a non-toxic form and this is associated with elevated production of ferritin. The accumulation of iron in the lung macrophages of hepcidin KO mice contrasts with splenic and hepatic macrophages which contain low iron levels as we have previously reported. Hepc KOliv mice with liver-specific hepcidin deficiency demonstrated same pulmonary iron overload profile as the Hepc KO mice, suggesting that pulmonary hepcidin is not critical in maintaining local iron homeostasis. In addition, the high iron load in the lung of Hepc KO mice does not appear to enhance acute lung inflammation or injury. Lastly, we have shown that intraperitoneal LPS injection is not associated with pulmonary hepcidin induction, despite high levels of inflammatory cytokines. However, intranasal LPS injection stimulates a hepcidin response, likely derived from alveolar macrophages, and alters pulmonary iron content in Hepc KO mice.